The influence of spiritual transformational leadership and religious motivation on spiritual performance - Maharani, Evita; Setiawan, Harry; Hasanudin, Hasanudin; Shalahuddin, Ahmad (Institute of Computer Science (IOCS), 2025)
A school or organization depends on how well its employees perform. Professional human resources tailored to individual ability tasks determine employee performance. The performance of employees as human resources is very important to achieve the vision, mission and goals of the organization. The type of leadership used by an organization greatly influences its success. Spiritual transformational leadership can encourage employees to achieve organizational goals based on positive spiritual values. Ultimately, this can result in improved employee performance in a more productive manner. The purpose of this study was to examine the effect of spiritual transformational leadership and religious motivation on the spiritual performance of MAN teachers in Pontianak City, both significantly and insignificantly, by including OCB as a mediating variable. This study used a quantitative approach by collecting data through an online survey using google form. The sample results amounted to 108 MAN teachers in Pontianak City, which included civil servants, and PPPK using purposive sampling technique. Structural Equation Modeling (SEM), using the Smart PLS 4 statistical tool, was used to quantify the data. The results of the statistical analysis showed that spiritual transformational leadership had no significant impact on spiritual performance, while spiritual transformational leadership had a significant impact on Organizational Citizenship Behaviour (OCB). In addition, religious motivation has a significant impact on OCB and spiritual performance, and OCB has a noticeable influence on spiritual performance, serving as both an independent variable and a mediating variable for religious motivation and spiritual transformational leadership.